The pigeon finds a hot dog! [videorecording (DVD)] : and more stories by Mo Willems. - Willems, Mo; Willems, Trixie; Cher, 1946- (Scholastic : Distributed in the U.S. by New Video, 2011)
Pigeon finds a delicious hot dog, but a sly and hungry duckling comes along who also wants a bite. Who will be the more clever bird? Help kids enhance reading skills, cooperation skills, and problem-solving skills in an enjoyable and entertaining way! Additional stories include Knuffle Bunny Too: A Case of Mistaken Identity; and Naked Mole Rat Gets Dressed.